Clinical psychology : concepts, methods, and profession - Phares, E. Jerry (Homewood, Ill. : Dorsey Press, 1984)
Including cutting-edge trends and new material throughout, this Seventh Edition of Clinical Psychology offers an introduction to the field. Author Timothy J. Trull explores empirically supported assessment methods and interventions; current trends in managed health care; culture, gender, and ethnicity considerations; and the influence of biological and genetic viewpoints, as well as the most progressive models being used today to train students for successful careers as clinical psychologists.
Includes bibliographical references and index.
Keywords: Clinical psychology; Psychotherapy